2016
DOI: 10.3390/nu8090570
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Athletes’ and Coaches’ Nutrition Knowledge and Reflections on the Quality of Current Nutrition Knowledge Measures

Abstract: Context: Nutrition knowledge can influence dietary choices and impact on athletic performance. Valid and reliable measures are needed to assess the nutrition knowledge of athletes and coaches. Objectives: (1) To systematically review the published literature on nutrition knowledge of adult athletes and coaches and (2) to assess the quality of measures used to assess nutrition knowledge. Data Sources: MEDLINE, CINAHL, SPORTDiscuss, Web of Science, and SCOPUS. Study Selection: 36 studies that provided a quantita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
217
9
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(243 citation statements)
references
References 51 publications
14
217
9
3
Order By: Relevance
“…This seems to be rare in this field, computing this construct falls in line with what Trackman et al [8] proposed. Concurrent validity is a measure of how well a particular test correlates with a previously validated measure and contributes to estimating the precision of the tool.…”
Section: Discussionsupporting
confidence: 83%
“…This seems to be rare in this field, computing this construct falls in line with what Trackman et al [8] proposed. Concurrent validity is a measure of how well a particular test correlates with a previously validated measure and contributes to estimating the precision of the tool.…”
Section: Discussionsupporting
confidence: 83%
“…The current questionnaire includes 32 questions (95 parts) addressing macronutrients and general nutrition, as such the range and quantity of these questions are similar to that of a previously validated general nutrition knowledge questionnaire for adults [21], additionally a further 33 questions (50 parts) address hydration and sport specific nutrition, thus provide sufficient information for conclusions to be drawn about the specific areas of the individuals general and or sport nutrition knowledge. Furthermore using the rating scores outlined in a recent systematic review [15] the current study meets all the criteria required to confirm validity and reliability, and is only the second questionnaire to do so [14]. Also the current questionnaire would score around 9 -10 out 11 (81 -91%) on the comprehensiveness rating, outscoring the other valid and reliable questionnaire [14] by~5 points (~45%).…”
Section: Discussionmentioning
confidence: 86%
“…A recent systematic review [15] highlighted 38 studies which have used a nutrition knowledge questionnaire, only one [14] of which met the full validity and reliability criteria. Furthermore with regards to comprehensiveness rating [15] the four questionnaires which scored highest on validity and reliability [14,[16][17][18] scored between 36 and 55% on comprehensiveness rating. There is a clear need for a psychometrically validated nutrition knowledge measure that can investigate the participant's general and sport nutrition knowledge and the aims of this research were to develop a valid and reliable general and sport nutrition knowledge questionnaire for athletes.…”
Section: Introductionmentioning
confidence: 99%
“…Trakman, et al (2016) concluded that there was difficulty in the assessment of nutrition knowledge in athletes. As a result, all athletes should follow specific nutritional strategies before, during and after training and competition to enhance their physical and mental performance (The Nutrition Working Group of Medical and Scientific Commission of International Olympic Committee, 2016).…”
Section: Discussionmentioning
confidence: 99%